DOES BREASTFEEDING OR NOT AFFECT A BETTER MATERNAL QUALITY OF LIFE? : LITERATURE REVIEW - Aulia Rahma Oktaviya; Gatut Hardianto; Budi Utomo; Ivon Diah Wittiarika (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2020)
Quality of life is important to achieve the best performance of mothers. Maternal quality of life is usually measured by WHOQOL-BREF standards (quality of life of the World Health Organization-BREF), SF-36 (Short-36), or MGI (Mother Generated Index). One factor that affects the maternal quality of life is breastfeeding. The practice of breastfeeding is the mother who is breastfeeding (giving only breast milk) and the mother who is not breastfeeding (with formula milk) as well as seeing the length of breastfeeding time for less than 6 months or more than 6 months. This literature review has research question with PICO standard to get the aim about the correlation between the practice of breastfeeding and maternal quality of life. 466 literatures were obtained from the SCOPUS, Proquest, Google Scholar, PubMed and EBSCOhost databases. Literature screening is done by looking at the inclusion and exclusion criteria that have been set so that 10 literatures will be reviewed. Most of the literature reports that mothers who breastfeed and continue to breastfeed even though only a month has a better quality of life than mothers who did not breastfeed. One study said that breastfeeding causes a decrease in the maternal quality of life, as well as several other studies that found no significant correlation between breastfeeding practices and maternal quality of life. This result can be used as a reference for the health policy to promote breastfeeding and quality of life.